Changing Codes and Changing Constitutions - Kong, Hoi (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2005)
In this article, the author addresses a neglected area of study, namely codal amendment in Canada. The author argues that the theoretical justi-fcations for the Civil Code of Québec and its distinctive design features raise concerns about how the Code is currently amended. In response to these concerns, the author draws on the rich literature concerning law reform in Canada to propose a reform institute that is charged with overseeing the process of codal amendment. Moreover, the author contends that when Canadian courts and Parliament respond to and the Quebec legislature effects changes to codal text they should be closely attentive to the purposes underlying the constitutional division of powers. To illustrate this last contention, the author critiques the Federal Law — Civil Law Harmonization Act, No. 1 and recent legislative and judicial developments respecting marriage and the civil union.